2000
DOI: 10.1177/096120330000900708
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid hemorrhage and systemic lupus erythematosus

Abstract: The frequency, clinical profile, treatment and outcome of subarachnoid hemorrhage (SAH) in patients with systemic lupus erythematosus (SLE) were assessed retrospectively, based on the case records of SLE of the Jichi Medical School Hospital over a 20 year period. Clinically defined SAH was found in 10 (3.9%) out of 258 SLE patients, which represented a frequency higher than previously assumed. Five patients had active SLE and lacked an apparent cause of SAH, other than SLE. A high mortality rate (5/5), no visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 14 publications
(3 reference statements)
5
52
0
1
Order By: Relevance
“…22 Their association is mediated by vasculitis. A recent case-control study has reported that transfusion was associated with the development of systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…22 Their association is mediated by vasculitis. A recent case-control study has reported that transfusion was associated with the development of systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is in accordance with clinical experiences in which IA is often found in subjects with autoimmune diseases. 29,30 Further studies are needed to strengthen our hypothesis. In addition, the present results might pave the way for an investigation of a link between immunologic events and IA development.…”
Section: Inoue Et Al Tnfrsf13b and Intracranial Aneurysm 2007mentioning
confidence: 81%
“…The incidence of subarachnoid hemorrhage (SAH) in SLE patients is low, 10) with frequency ranging from 0.93% to 3.9%. 2,12) Analysis of 57 Japanese patients with SAH associated with SLE found 38 patients had cerebral aneurysms. 17) Neurosurgical procedures, such as surgical clipping, were performed in 22 patients.…”
Section: Discussionmentioning
confidence: 99%